CFD simulation aided glass quality and energy efficiency analysis of an oxy-fuel glass melting furnace with electric boosting. (August 2022) - Raič, Juraj; Wachter, Philipp; Hödl, Philipp; Demuth, Martin; Gaber, Christian; Gerhardter, Hannes; Prieler, René; Hochenauer, Christoph
Highlights: Inexpensive coupled CFD simulations of glass furnace with verified numerical models. Link between specific power input and glass quality was established and quantified. Space utilisation increased when specific heat input over free glass surface increased. Space utilisation increased when pull rate was reduced or fuel mass flow increased. Abstract: Determining glass quality has been a focal point of CFD studies of glass furnaces for several decades. Previous research identified the utilisation of glass tank space by inhomogeneities as a crucial quantity for the scrutinization of glass quality. However, the majority of previous CFD based parametric studies were conducted on idealized glass tank models, which neglected the influence of the turbulent gas phase in the combustion chamber on the heat transfer. Consequently, not all of the findings are universally applicable in practical settings. Hence, the present work aims at closing this research gap by introducing two improvements over the current state-of-the-art in a parametric study by: 1) Employing a verified, computationally inexpensive, coupled numerical model in the complete CFD simulation of a glass melting furnace and 2) Establishing and quantifying the link between variations of the specific power input and common glass quality indicators. It was shown that due to the cross-fired configuration of the burners, increasing the specific power input over the free glass surface resulted in higher transversal velocities and temperature gradients, which favoured the development of helical flow in the melt and thus increased the critical residence time and by extension, the glass quality.